PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN AKHLAKUL KARIMAH DI SMKN 5 MALANG - Silviana Silviana; Ibnu Jazari; Fita Mustafida (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Education is an important aspect in the development of national morals, especially student morale. Change in human life that occur only see the sciences in the world of education. Knowledge is the result of data sourced from studies that are realized through books or online-based educational learning systems without looking at the basis of amar ma’ruf nahi munkar. Islamic religious education teachers have a role in instilling moral compassion for their students. Researchers use a qualitative approach to the type of case study research. Data collection techniques using interviewes, observation, and documentation.